Regulating AI: Challenges and the Way Forward Through Regulatory Sandboxes - Yordanova, Katerina; Bertels, Natalie (Multidisciplinary Perspectives on Artificial Intelligence and the Law, 2024)
Financial industry was the first filed where it became clear that we needed a new type of regulation, an evolutionary and anticipatory approach that can at least stand chance to mitigate the new risks posed by disruptive technologies such as artificial intelligence (AI). This approach took the shape of various tools, none of which has showed more prominence than the regulatory sandboxes. This rather young approach to regulation spread across various sectors and jurisdictions from FinTech to privacy and healthcare.